Organic matter concentration and characteristic dynamics in surface waters post-bushfires and cyclones: fDOM sensors for environmental monitoring and control - Daraei, Hiua; Bertone, Edoardo; Stewart, Rodney A; Awad, John; Leavesley, Adam; Gale, Matthew; Jones, Eriita; Cinque, Kathy; Agnew, Mark; Burger, Hugh A; Van Leeuwen, John (2024)
This study presents the findings of an investigation on the dynamics of dissolved organic matter (DOM) concentration and characteristics of four Australian rivers and reservoirs after their catchments had been severely burned by bushfires (wildfires) or impacted by a tropical cyclone. Dissolved organic carbon (DOC) increased immediately following the events, and subsequently decreased. The findings indicate rapid stabilisation of water quality, based on the measured parameters, following the commencement of the first winter after the events (which occurred in mid/end summer). In the fire-affected Middle River catchment, DOC decreased from 30.7 mg L−1 to 10.2 mg L−1 over approximately seven months. In the case of the Herring Lagoon catchment, which was affected by cyclone Uesi, DOC decreased from 15.6 mg L−1 to 1.2 mg L−1 over approximately ten months. However, the DOM present in the surface water exposed to the cyclone showed higher molecular weight, coagulability and UV-vis absorbance than the DOM present in the surface water of fire-affected catchments. The observed rapid increase and then reduction in DOM concentrations after extreme climate events indicates the need for short-term and rapid responses for drinking water treatment. The fluorescence signal of a field-deployable fluorescent DOM (fDOM) sensor showed potential as an online monitoring tool for assessing DOM concentration in surface waters, including under extreme conditions. The rapid identification of high DOM loadings in surface waters following extreme climate events (e.g. using a field deployed fDOM sensor) along with its coagulability characteristics could assist in catchment management and drinking water treatment by enabling timely control decisions in response to the impacts of such events.